A simple three step method for selective placement of organic groups in mesoporous silica thin films - Franceschini, Esteban Andrés; de la Llave, Ezequiel Pablo; Williams, Federico José; Soler Illia, Galo Juan de Avila Arturo (Elsevier Science Sa, 2016)
Fil: Franceschini, Esteban Andrés. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina